PENGARUH EFIKASI DIRI DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI MATEMATIKA SISWA - Cahyani, Lidya Indah Dwi; Hadiprasetyo, Krisdianto (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
This study aims to determine the effect of emotional intelligence and self-efficacy on the mathematics achievement of X E1 students of Veteran Sukoharjo High School. This study used a quantitative approach, and data were collected through questionnaires. Students in class X E1 SMA Veteran Sukoharjo were the subjects of this study. SPSS 23 software was used to assist in analyzing the data of this study. The data obtained will be tested for classical assumptions in multiple linear regression, which includes a normality test, a multicollinearity test, a heteroscedasticity test, and an auto autocorrelation test. Then multiple linear regression analysis will be carried out and the results of the Simultaneous Test (F test) are obtained with a significant level of , it can be concluded that  is accepted or  is rejected, which means that self-efficacy () and emotional intelligence () have no significant effect on math achievement (). The result of this study is that 14.7% of self-efficacy and emotional intelligence can affect student math achievement, while 85.3% is influenced by other things. From this study, it can be concluded that: (a) self-efficacy and emotional intelligence do not significantly affect student achievement in mathematics; (b) self-efficacy does not significantly affect student achievement in mathematics; and (c) emotional intelligence does not significantly affect student achievement in mathematics.